The Dynamics of Anomaly Voters: Responding to Bawaslu Findings in the 2019 Election in Riau - Alexsander Yandra; Adrian Faridhi; Andrizal Andrizal; Suyito Suyito (Journal of Governance and Public Policy, 2023)
This study tries to examine the findings of the election supervisory body (Bawaslu) regarding 32,556 anomaly voters ahead of the 2019 general election in Riau. This trend occurs because of the unsynchronization of data from the Regional General Election Commission (KPUD), the Central Statistics Agency (BPS) and the Population and Civil Registration Office (Disdukcapil) of Riau Province. Findings in the form of poor accuracy in determining the voter list by the KPUD of Riau Province have caused dynamics and polemics in the community. By using the concepts of Election theory and Democracy and Community Political Rights with a single case qualitative approach, this study finds that the potential for people whose data is not recorded by the Disdukcapil will not only lose their right to vote in elections but can also lead to potential violations of Human Rights. Therefore, this study tries to provide an early warning about the potential negative consequences of inaccurate voter data.